Halal Marketing as a Strategic Approach to Enhance Service Quality in Muslim Consumer Markets - Mulyandi, M. Rachman; Angelika, Natalia; Gunawan, Angga; Kireina, Tesalonita (Journal of Islamic Studies and Education, 2025)
The purpose of this research is to discuss the literature study of the relationship between the application of halal marketing in the industrial world and its relation to the quality of service provided by the industry. The primary focus of this study is the relationship between the application of halal marketing in the industry and its impact on the quality of services provided. Halal Marketing not only introduces uniqueness in product marketing approaches but also emphasizes intangible service aspects that must be conducted according to halal principles. Quality service dimensions such as trust, satisfaction, and loyalty are key points evaluated in the context of Muslim consumers. The research method used in this study uses a systematic literature review method is a rigorous and structured research method aimed at identifying, evaluating, and synthesizing all relevant studies related to a specific research question or topic. The result of this study is the application of the use of Halal Marketing as one of the strategies used by the industry can improve the quality of service provided by the industry. With the increasing quality of service, it will lead to customer satisfaction and loyalty from the industry. Furthermore, halal marketing supports the muslim lifestyle through tangible, trustworthy, and responsive  services that build trust and customer satisfaction. This study strengthens the position of halal marketing as an effective strategy that is not only financially beneficial but also adds social and religious value for industry practitioners and Muslim consumers.